Introduction: Farm Workers, Collective Bargaining Rights, and the Meaning of Constitutional Protection - Fudge, Judy (Constitutional Labour Rights in Canada: Farm Workers and the Fraser Case, 2012)
Explains in detail the purpose of the book (see publisher's description) and provides a synopsis of the essays contained therein.
Keywords: Agricultural laborers; Canada. Collective bargaining; Canada. Employee rights; Canada. Freedom of association; Canada. Liberté d'association; Canada. Migrant agricultural laborers; Canada. Négociations collectives; Canada. Personnel; Canada. Travailleurs agricoles; Canada. Travailleurs agricoles migrants; Droit; Droits; Law and legislation; Legal status, laws, etc.